Electrostatic force spectroscopy revealing the degree of reduction of individual graphene oxide sheets - Shen, Yue; Wang, Ying; Zhou, Yuan; Hai, Chunxi; Hu, Jun; Zhang, Yi (Beilstein Journal of Nanotechnology, 2018)
Electrostatic force spectroscopy (EFS) is a method for monitoring the electrostatic force microscopy (EFM) phase with high resolution as a function of the electrical direct current bias applied either to the probe or sample. Based on the dielectric constant difference of graphene oxide (GO) sheets (reduced using various methods), EFS can be used to characterize the degree of reduction of uniformly reduced one-atom-thick GO sheets at the nanoscale. In this paper, using thermally or chemically reduced individual GO sheets on mica substrates as examples, we characterize their degree of reduction at the nanoscale using EFS. For the reduced graphene oxide (rGO) sheets with a given degree of reduction (sample n), the EFS curve is very close to a parabola within a restricted area. We found that the change in parabola opening direction (or sign the parabola opening value) indicates the onset of reduction on GO sheets. Moreover, the parabola opening value, the peak bias value (tip bias leads to the peak or valley EFM phases) and the EFM phase contrast at a certain tip bias less than the peak value can all indicate the degree of reduction of rGO samples, which is positively correlated with the dielectric constant. In addition, we gave the ranking of degree for reduction on thermally or chemically reduced GO sheets and evaluated the effects of the reducing conditions. The identification of the degree of reduction of GO sheets using EFS is important for reduction strategy optimization and mass application of GO, which is highly desired owing to its mechanical, thermal, optical and electronic applications. Furthermore, as a general and quantitative technique for evaluating the small differences in the dielectric properties of nanomaterials, the EFS technique will extend and facilitate its nanoscale electronic devices applications in the future.
Keywords: degree of reduction; dielectric property; electrostatic force microscopy; electrostatic force spectroscopy; graphene oxide

(untitled) - Lee, C.; Wei, X.; Kysar, J. W.; Hone, J. (Science, 2008)

(untitled) - Balandin, A. A.; Ghosh, S.; Bao, W.; Calizo, I.; Teweldebrhan, D.; Miao, F.; Lau, C. N. (Nano Lett., 2008)

(untitled) - Orlita, M.; Faugeras, C.; Plochocka, P.; Neugebauer, P.; Martinez, G.; Maude, D. K.; Barra, A. L.; Sprinkle, M.; Berger, C.; de Heer, W. A.; Potemski, M. (Phys. Rev. Lett., 2008)

(untitled) - Castro Neto, A. H.; Guinea, F.; Peres, N. M. R.; Novoselov, K. S.; Geim, A. K. (Rev. Mod. Phys., 2009)

(untitled) - Kim, K. S.; Zhao, Y.; Jang, H.; Lee, S. Y.; Kim, J. M.; Kim, K. S.; Ahn, J.-H.; Kim, P.; Choi, J.-Y.; Hong, B. H. (Nature, 2009)

(untitled) - Pei, S. F.; Cheng, H. M. (Carbon, 2012)

(untitled) - López, V.; Sundaram, R. S.; Gómez-Navarro, C.; Olea, D.; Burghard, M.; Gómez-Herrero, J.; Zamora, F.; Kern, K. (Adv. Mater., 2009)

(untitled) - Yang, D.; Velamakanni, A.; Bozoklu, G.; Park, S.; Stoller, M.; Piner, R. D.; Stankovich, S.; Jung, I.; Field, D. A.; Ventrice, C. A., Jr; Ruoff, R. S. (Carbon, 2009)

(untitled) - Zhang, J.; Yang, H.; Shen, G.; Cheng, P.; Zhang, J.; Guo, S. (Chem. Commun., 2010)

(untitled) - Shen, Y.; Guo, S.; Hu, J.; Zhang, Y. (Appl. Phys. Lett., 2012)

(untitled) - Zhou, Y.; Bao, Q.; Tang, L. A. L.; Zhong, Y.; Loh, K. P. (Chem. Mater., 2009)

(untitled) - Kumar, P. V.; Bardhan, N. M.; Tongay, S.; Wu, J.; Belcher, A. M.; Grossman, J. C. (Nat. Chem., 2014)

(untitled) - Gao, L.; Ren, W.; Li, F.; Cheng, H.-M. (ACS Nano, 2008)

(untitled) - Gómez-Navarro, C.; Meyer, J. C.; Sundaram, R. S.; Chuvilin, A.; Kurasch, S.; Burghard, M.; Kern, K.; Kaiser, U. (Nano Lett., 2010)

(untitled) - Wei, Z.; Wang, D.; Kim, S.; Kim, S.-Y.; Hu, Y.; Yakes, M. K.; Laracuente, A. R.; Dai, Z.; Marder, S. R.; Berger, C.; King, W. P.; de Heer, W. A.; et al. (Science, 2010)

(untitled) - Zhang, K.; Fu, Q.; Pan, N.; Yu, X.; Liu, J.; Luo, Y.; Wang, X.; Yang, J.; Hou, J. (Nat. Commun., 2012)

(untitled) - Ekiz, O. Ö.; Ürel, M.; Güner, H.; Mizrak, A. K.; Dâna, A. (ACS Nano, 2011)

(untitled) - Hu, J.; Xiao, X.-D.; Salmeron, M. (Appl. Phys. Lett., 1995)

(untitled) - Hu, J.; Xiao, X.-D.; Ogletree, D. F.; Salmeron, M. (Science, 1995)

(untitled) - Shen, Y.; Zhou, Y.; Sun, Y.; Zhang, L.; Wang, Y.; Hu, J.; Zhang, Y. (Appl. Surf. Sci., 2017)

(untitled) - Shen, Y.; Wang, Y.; Zhang, J.; Hai, C.; Zhou, Y.; Hu, J.; Zhang, Y. (J. Appl. Phys., 2014)

(untitled) - Shen, Y.; Wang, Y.; Zhou, Y.; Shi, A.; Hu, J.; Zhang, Y. (J. Phys. D: Appl. Phys., 2016)

(untitled) - Verdaguer, A.; Cardellach, M.; Segura, J. J.; Sacha, G. M.; Moser, J.; Zdrojek, M.; Bachtold, A.; Fraxedas, J. (Appl. Phys. Lett., 2009)

(untitled) - Lu, W.; Wang, D.; Chen, L. (Nano Lett., 2007)

(untitled) - Shen, Y.; Zhang, Y.; Hu, J. (J. Chin. Electron Microsc. Soc., 2013)

(untitled) - Kulkarni, D. D.; Kim, S.; Chyasnavichyus, M.; Hu, K.; Fedorov, A. G.; Tsukruk, V. V. (J. Am. Chem. Soc., 2014)

(untitled) - Burnett, T.; Yakimova, R.; Kazakova, O. (Nano Lett., 2011)

(untitled) - Kurra, N.; Prakash, G.; Basavaraja, S.; Fisher, T. S.; Kulkarni, G. U.; Reifenberger, R. G. (Nanotechnology, 2011)

(untitled) - El Khoury, D.; Arinero, R.; Laurentie, J. C.; Castellon, J. (AIP Adv., 2016)

(untitled) - de Tournadre, G.; Reisdorffer, F.; Rödel, R.; Simonetti, O.; Klauk, H.; Giraudet, L. (J. Appl. Phys., 2016)

(untitled) - He, H.; Klinowski, J.; Forster, M.; Lerf, A. (Chem. Phys. Lett., 1998)

(untitled) - Schniepp, H. C.; Li, J.-L.; McAllister, M. J.; Sai, H.; Herrera-Alonso, M.; Adamson, D. H.; Prud'homme, R. K.; Car, R.; Saville, D. A.; Aksay, I. A. (J. Phys. Chem. B, 2006)

(untitled) - Hummers, W. S., Jr; Offeman, R. E. (J. Am. Chem. Soc., 1958)

(untitled) - Zhou, X.; Lu, G.; Qi, X.; Wu, S.; Li, H.; Boey, F.; Zhang, H. (J. Phys. Chem. C, 2009)

(untitled) - Eda, G.; Mattevi, C.; Yamaguchi, H.; Kim, H.; Chhowalla, M. (J. Phys. Chem. C, 2009)

(untitled) - Kendall, T. A.; Martin, S. T. (J. Phys. Chem. A, 2006)